NRG1 fusion-driven tumors: biology, detection, and the therapeutic role of afatinib and other ErbB-targeting agents - Laskin, Janessa; Liu, S. V.; Tolba, Khaled A.; Heining, Christoph; Schlenk, Richard Friedrich; Cheema, P.; Cadranel, J.; Jones, M. R.; Drilon, A.; Cseh, A.; Gyorffy, S.; Solca, F.; et al. (Annals of oncology, 2020)
Oncogenic gene fusions are hybrid genes that result from structural DNA rearrangements, leading to deregulated activity. Fusions involving the neuregulin-1 gene (NRG1) result in ErbB-mediated pathway activation and therefore present a rational candidate for targeted treatment. The most frequently reported NRG1 fusion is CD74-NRG1, which most commonly occurs in patients with invasive mucinous adenocarcinomas (IMAs) of the lung, although several other NRG1 fusion partners have been identified in patients with lung cancer, including ATP1B1, SDC4, and RBPMS. NRG1 fusions are also present in patients with other solid tumors, such as pancreatic ductal adenocarcinoma. In general, NRG1 fusions are rare across different types of cancer, with a reported incidence of <1%, with the notable exception of IMA, which represents ≈2%-10% of lung adenocarcinomas and has a reported incidence of ≈10%-30% for NRG1 fusions. A substantial proportion (≈20%) of NRG1 fusion-positive non-small-cell lung cancer cases are nonmucinous adenocarcinomas. ErbB-targeted treatments, such as afatinib, a pan-ErbB tyrosine kinase inhibitor, are potential therapeutic strategies to address unmet treatment needs in patients harboring NRG1 fusions.
Gesehen am 11.01.2021